2018
DOI: 10.1016/j.ajo.2017.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Two Phase 3 Clinical Trials Comparing the Safety and Efficacy of Netarsudil to Timolol in Patients With Elevated Intraocular Pressure: Rho Kinase Elevated IOP Treatment Trial 1 and 2 (ROCKET-1 and ROCKET-2)

Abstract: In 2 large, randomized, double-masked trials reported here, once-daily dosing of netarsudil 0.02% was found to be effective and well tolerated for the treatment of patients with ocular hypertension and open-angle glaucoma. The novel pharmacology and aqueous humor dynamic effects of this molecule suggest it may be a useful addition to the armamentarium of ocular hypotensive medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
222
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(258 citation statements)
references
References 27 publications
15
222
1
Order By: Relevance
“…No treatment-related serious AEs were reported in any treatment arm ( Cornea verticillata was reported in 15.4% (74/482) of patients receiving netarsudil/latanoprost FDC, 11.6% (58/498) of those receiving netarsudil, and no patients (0/488) receiving latanoprost. This frequency was as observed in previous studies with netarsudil [15]. Most cases of cornea verticillata were mild: 98.6% (73/74) of affected patients treated with netarsudil/latanoprost FDC and 96.6% (56/58) of affected patients treated with netarsudil.…”
Section: Safetysupporting
confidence: 88%
See 1 more Smart Citation
“…No treatment-related serious AEs were reported in any treatment arm ( Cornea verticillata was reported in 15.4% (74/482) of patients receiving netarsudil/latanoprost FDC, 11.6% (58/498) of those receiving netarsudil, and no patients (0/488) receiving latanoprost. This frequency was as observed in previous studies with netarsudil [15]. Most cases of cornea verticillata were mild: 98.6% (73/74) of affected patients treated with netarsudil/latanoprost FDC and 96.6% (56/58) of affected patients treated with netarsudil.…”
Section: Safetysupporting
confidence: 88%
“…Netarsudil, a Rho kinase (ROCK) inhibitor, was approved by the US Food and Drug Administration in December 2017 for reducing IOP in patients with OAG or OHT [10]. Netarsudil targets the underlying pathophysiology of elevated IOP, increased trabecular outflow resistance, and thereby increases trabecular outflow and reduces IOP [11][12][13][14][15][16]. Latanoprost, the most commonly prescribed prostaglandin analogue, has a complementary mechanism of action, lowering IOP by increasing uveoscleral outflow [9,17].…”
Section: Introductionmentioning
confidence: 99%
“…Even though dysfunction of the trabecular outflow pathway is responsible for elevated IOP, clinically, most of IOP-lowering medications target the unconventional outflow pathway or secretion. New medications targeting the predominant drainage pathway (the TM pathway) are in high demand, including two recently approved medications (8, 12, 13). Thus, rho kinase inhibitors and nitric oxide drugs are the results of research over the last 25 years that identified important regulatory processes in the trabecular outflow pathway (8).…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous humor production is reduced primarily through its action on the norepinephrine transporter, while the inhibition of Rho-kinase reduces stiffness [26] and stress fibers in the TM as seen with other Rho-kinase inhibitors [30] . The impact on vessel diameters is variable, but in clinical use, conjunctival hyperemia is a common observation [31] and probably caused by rendering vascular smooth muscle cells less sensitive to intracellular Ca 2+ [32] .…”
Section: Discussionmentioning
confidence: 99%